The sound of silence: stillness and quiet-a case study of the role of Christian meditation in children's prayer life - Hyde, Brendan (Journal of Religious Education, 2014)
This research explored the role of Christian meditation-as one particular prayer form-in enhancing the relational lives of children, in particular, their relationship with God. An instrumental case study was used, in which the focus was on a specific issue (the role of Christian meditation as one particular prayer form in enhancing the relational lives of children) and where the case (the Catholic primary school) became a vehicle to enable the researchers to better understand this issue. Time sampling observation charts were used to record the behaviour of up to six children during the meditation. These were subsequently written up as short narratives describing the behaviours exhibited by the students, and then plotted using Berryman's modes of being (quiet, silence) and vectors of movement (stillness as sound, stillness as movement). The analysis revealed that, for the most part, students remained focused, still, quiet and attentive during the meditation exercises as well in the follow up learning activities. Quiet (mode of being) was experienced as an inner motivation with a movement towards both stillness as movement and stillness as sound, suggesting that the practice of meditation had opened the possibility that God might be present in the stillness and silence, thereby potentially enhancing their relationship with God.